HOSPICE UTILIZATION AND PLACE OF DEATH BY DEMENTIA DIAGNOSIS AND RACE/ETHNICITY. (20th December 2022) - Jarrín, Olga; Lin, Haiqun; Wu, Bei; Duberstein, Paul; Lopez, Maria; Zafar, Anum
Abstract: Timing of hospice referral is critical to patient's and family's quality of life and satisfaction with hospice care. This study examined racial/ethnic variation in hospice use and factors associated with death at home among Medicare beneficiaries aged 50 years and older who died in 2018 (n=1, 998, 282). Hospice use was most frequent among non-Hispanic white beneficiaries (55.8%) followed by Hispanic (46.2%), Asian American (44.5%), Black (42.7%), and American Indian (42.1%) beneficiaries. Among decedents diagnosed with dementia, initiation of hospice prior to the last day of life was significantly associated with death at home among all racial/ethnic groups: non-Hispanic white (OR=2.62), Black (OR=2.04), Hispanic (OR=2.17), Asian American (OR=2.54), and American Indian (OR=2.76). Among decedents not diagnosed with dementia, initiation of hospice prior to the last day of life was less strongly associated with death at home: white (OR=1.33), Black (OR=0.83), Hispanic (OR=1.32), Asian American (OR=1.69), and American Indian (OR=1.56).